Sensitization of cisplatin resistant bladder tumor by combination of cisplatin treatment and co-culture of dendritic cells with apoptotic bladder cancer cells - Zhang, Qi; Chen, Zhuo (Cellular and Molecular Biology, 2018)
Dendritic cells (DCs) are a population of professional antigen presenting cells (APCs), serving as central regulators of adaptive immunity by presenting antigens. In addition, DCs play essential roles in the connection of the innate and adaptive immune responses. Recently, therapeutic vaccines turn out to become a viable therapeutic approach for immunotherapy of cancers. Here we report a dendritic cell-based vaccine strategy which could suppress the bladder tumor growth in vivo and improve the efficiency of chemotherapy. In this study, we investigate the antitumor effects of mature DCs induced by antigen loading in bladder tumor in vivo. We demonstrate the co-culture of cisplatin induced apoptotic human bladder cancer cell line, T24 cells with immature DCs could promote the maturation of DCs. Cisplatin and these activated DCs were reintroduced into mice bearing the T24 cisplatin resistant cells-derived tumor growth to activate or boost the immune response. Mice with iDCs co-cultured with apoptotic T24 (iDCs T24 Apo) cells injection effectively initiate a cytotoxic effect against tumor growth and improve the survival rates of mice compared with controls. Moreover, we observed injection of iDCs T24 apoptosis cells combined with cisplatin into mice with T24 cisplatin resistant cancer cells-derived tumor resulted in a statistically significant suppression of tumor growth compared with mice injected with PBS alone, cisplatin alone, iDCs, iDCs T24 Apo cells, cisplatin plus iDCs. This study provides a dendritic cell-based vaccine strategy which might reduce the risk of tumor recurrence and improve the efficiency of anti-chemoresistance of bladder cancer.